The Impact of Qat Chewing on Health and Social Life: A Cross-Sectional Study Among Yemeni Adults - Algutaini, Safana Abdullah; Al-Ameri, Aziz; Ali Mahyoub Abdo , Basheer (Journal of Medical Health Research and Psychiatry, 2024)
Background: Qat chewing is a widespread social practice in many regions, notably in Yemen and East Africa, with increasing prevalence. While traditionally rooted in cultural and social gatherings, its health and social impacts remain a growing concern. This study aims to explore the demographic patterns of qat chewing, the health issues associated with its use, and the social implications among different population groups. Methods: A cross-sectional survey was conducted, including 920 participants from various demographic groups. Data were collected on age, gender, educational level, occupation, frequency of qat chewing, health issues, and attempts to quit. Statistical analyses were performed to examine correlations between qat chewing behaviors, health outcomes, and social perceptions. Results: The majority of qat chewers were aged between 18-24 years (66%), and the practice was more prevalent among males (67%). Frequent qat chewers, especially those who chew daily, reported higher incidences of health issues, with dental problems (41%), weight loss (32%), and gastrointestinal issues (22%) being the most common. Educational level and occupation significantly impacted health outcomes; participants with higher education were more likely to report weight loss and gastrointestinal issues, while unemployed individuals reported the highest incidence of health problems. Social Impact: Qat chewing is deeply embedded in social gatherings, with 61% of respondents viewing it as an important or very important part of social events. However, despite its cultural significance, 75% of respondents stated they would not encourage others to chew qat, reflecting growing awareness of its negative health and social consequences. Additionally, nearly 38% of respondents reported that qat chewing had a positive impact on their productivity, although 22% reported negative effects. Conclusion: The findings reveal that qat chewing, though culturally significant, is associated with various health risks and negative social perceptions. Public health interventions aimed at reducing qat use and addressing its health consequences are needed, particularly for younger populations and those in lower socioeconomic groups.